'Illegal' gold mining and the everyday in post-apartheid South Africa. Issue 173 (3rd July 2022) - Madimu, Tapiwa
ABSTRACT: This paper examines unregulated gold-mining activities prevalent at disused mines and decommissioned shafts at operating mines in post-apartheid South Africa. This kind of mining is deemed illegal by the government since it is outside the parameters of the country's main mining legislation. The author uses the concept of 'the everyday' to examine the daily living patterns and work operations of unregulated miners ( zama-zamas ) to fully understand their real world, beyond what is peddled by the state, and to argue that unregulated mining activities are orderly and make a significant contribution to the livelihoods of thousands of people in South Africa and the subregion. A thorough examination of their daily work and leisure routines sheds more light on their actual world, which has till now been obscured by government and media reports that emphasise the 'illegal' and violent aspects while remaining mute on the positive elements.